2023
DOI: 10.5761/atcs.ra.22-00125
|View full text |Cite
|
Sign up to set email alerts
|

Conventional Prostheses versus Sutureless Perceval for Aortic Valve Replacement: A Meta-Analysis

Abstract: Purpose: Perceval sutureless valves have gained popularity. Whether this implant performs superior to the traditional sutured prosthesis remains unclear. This metaanalysis compared the Perceval implants versus the sutured conventional valves for aortic valve replacement (AVR). Methods: This meta-analysis was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The following databases were accessed: PubMed, Google Scholar, Web of Science, Scopus, and EMBASE. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…A metaanalysis revealed no signi cant difference in early mortality, perioperative complications, and paravalvular leakage between the Perceval and conventional prosthesis groups. Moreover, a shorter CPB time, aortic cross-clamping time, and higher pacemaker implantation rate were observed in the Perceval group [11]. Some reports revealed that the authors did not experience more failures or PVL when using Perceval in multiple valve procedures, which corroborates recent ndings [10,12].…”
Section: Discussionsupporting
confidence: 81%
“…A metaanalysis revealed no signi cant difference in early mortality, perioperative complications, and paravalvular leakage between the Perceval and conventional prosthesis groups. Moreover, a shorter CPB time, aortic cross-clamping time, and higher pacemaker implantation rate were observed in the Perceval group [11]. Some reports revealed that the authors did not experience more failures or PVL when using Perceval in multiple valve procedures, which corroborates recent ndings [10,12].…”
Section: Discussionsupporting
confidence: 81%
“…A meta-analysis revealed no significant difference in early mortality, perioperative complications, and paravalvular leakage between the Perceval and conventional prosthesis groups. Moreover, a shorter CPB time, aortic cross-clamping time, and higher pacemaker implantation rate were observed in the Perceval group [ 11 ]. Some reports revealed that the authors did not experience more failures or PVL when using Perceval in multiple valve procedures, which corroborates recent findings [ 10 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…33,44 Still, in the absence of long-term data on PPI, the reliability of SV in younger patients is questionable. 45…”
Section: Discussionmentioning
confidence: 99%